Improving Employee Performance Through Work Motivation - Fajrin, Heru; B, Mesra (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
This research was conducted to determine the influence of organizational culture, work motivation on employee performance.In observations conducted by researchers at BPJS Employment Padang Sidimpuan and Lhokseumawe Branch Offices, there is an organizational culture phenomenon within it that has an influence on employee motivation and performance. There are differences in organizational culture within BPJS Employment Padang Sidimpuan and Lhokseumawe Branch Offices and other company offices. This can be seen from differences- in employee behavior to the regulations within them. As happened at the Padang Sidempuan branch of BPJS, where the employees' behavior was more communicative with each other than with the Lhoksumawe branch. Another difference is that the working hours at the Lhoksumawe branch of BPJS are more flexible than those at the Padang Sidempuan branch. This different organizational culture will of course result in different motivation and performance in each branch. Therefore, researchers are very interested in taking up this discussion. Based on the above background, the author is interested in conducting research entitled "The Influence of Organizational Culture on Employee Performance with Work Motivation as an Intervening Variable at "BPJS Employment Padang Sidimpuan and Lhokseumawe Branch Offices" The results of this research are as follows: Organizational Culture has a positive and significant effect on Employee Performance with an original sample value of 0.442 and a p value of 0.000. Organizational culture has a positive and significant effect on work motivation with an original sample value of 0.900 and a p value of 0.000. Work Motivation has a positive and significant effect on employee performance with an original sample value of 0.529 and a p value of 0.000. Organizational culture has a positive and significant indirect effect on employee performance through employee performance with an original sample value of 0.476 and a p value of 0.000.